1939
DOI: 10.1002/zaac.19392410401
|View full text |Cite
|
Sign up to set email alerts
|

Über Zweistoffsysteme mit Germanium. I. Germanium/Aluminium, Germanium/Zinn und Germanium/Silicium

Abstract: Nit 5 Abbildungen irn Text Es ist eine alte Erfahrung der Chemie, daB zwei Elemente miteinander uin so stabilere Verbindungen bilden, je verschiedener sie sind. Fruher haben sich die Chemiker in erster Linie mit solchen Systemen beschaftigt, in denen sehr stabile Terbindungen aus sehr verschiedenen Elementen gebildct werden, das heifit also mit den snlzartigen Verbindungen aus Metallen und Nichtmetallen. Es bedurfte schon einer verfeinerten Experimentierkunst, um auch solche Verbindungen zu bearbeiten, die nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
1
3

Year Published

1942
1942
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(66 citation statements)
references
References 3 publications
6
56
1
3
Order By: Relevance
“…As the layer thickness increase, the peaks in the phonon transmission disappear, due to the loss of the original momentum and random traveling directions of the phonons after scattering within a thick alloyed layer, i.e., strong mode conversion of the phonons across the alloyed layer. 47 The thermal conductance of the 2.27 nm alloy layer itself is estimated to be ~4.4 GW/m 2 K, which is significantly larger than the overall thermal conductance from our calculation. This indicates that the interface thermal resistance across the alloyed interface is mainly governed by the adjacent regions between the bulk materials and the alloyed layer, where atoms slightly deviate from their original position in a bulk crystal.…”
Section: Alloyed Interfacecontrasting
confidence: 52%
“…As the layer thickness increase, the peaks in the phonon transmission disappear, due to the loss of the original momentum and random traveling directions of the phonons after scattering within a thick alloyed layer, i.e., strong mode conversion of the phonons across the alloyed layer. 47 The thermal conductance of the 2.27 nm alloy layer itself is estimated to be ~4.4 GW/m 2 K, which is significantly larger than the overall thermal conductance from our calculation. This indicates that the interface thermal resistance across the alloyed interface is mainly governed by the adjacent regions between the bulk materials and the alloyed layer, where atoms slightly deviate from their original position in a bulk crystal.…”
Section: Alloyed Interfacecontrasting
confidence: 52%
“…Garg et al [22] has applied this approach to Si-Ge alloys using the force constants from DFPT and reached excellent with the experimental data [23,24].…”
Section: Alloy Modelingmentioning
confidence: 84%
“…Previous experimental and theoretical studies on Si-Ge alloys [22][23][24] have found dramatic decrease in the lattice thermal conductivity from pure Si and Ge.…”
Section: Introductionmentioning
confidence: 88%
“…One may note that the thermal conductivity of ≃1.3 Wcm −1 K −1 in Si at room temperature is almost reduced by an order of magnitude (≃0.1 Wcm −1 K −1 ) with alloying with Ge in Si-Ge alloys. 37,44 Thus with Sn being more massive, one may expect further reduction in the thermal conductivity in Si-Ge-Sn ternary alloys.…”
mentioning
confidence: 99%